Phylogenetic Study of Madura Cattle Based on Mitochondrial Cyt b and D-loop Sequences - Nirmala Fitria Firdhausi; Achmad Farajallah; Dyah Perwitasari (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
Madura Cattle is one breed of local cattle from Indonesia. Madura cattle are estimated to originate from a crossbreeding between Bos indicus and Bos javanicus. Another presumption is that Madura cattle are the result of a crossbreeding between B. indicus males and mixed B. javanicus or Bos taurus. Tracing the history of Madura cross and another cattle phylogenetic based on maternal lineage can be done by analyzing the variation of the mitochondrial genome (mtDNA). The purpose of this study was to determine the clarity of the origin of Madura cattle based on maternal lineage using mtDNA markers Cyt b and D-loop. This research is expected to provide genetic information and the origin of Madura cattle, so that it can be used to help improve the breeding and conservation program for Madura cattle. The results of the phylogeny tree reconstruction, using the Cyt b and D-loop genes showed that Madura cattle originated from Sampang region (Polagan, Golbung, and Komis) were grouped into two types of maternal origin. Madura cattle clade I are grouped with B. indicus and B. taurus, while Madura cattle clade II are grouped with B. javanicus. A crossbreeding between B. javanicus and B. indicus is estimated to have been carried out since the entry of Hindu culture brought by the India peoples to Indonesia around 1800 years ago. The crossing between B. javanicus and B. indicus was then more intensively carried out at the time of the government's promoting the development of Ongol cattles (B. indicus) in the days of the Dutch East Indies. The length segment of Cyt b that can be amplified is 230 bp and the D-loop segment of varying length, 577 bp for the Madura 41 and 29 samples, and 624 bp for sample 32.